Experimental Study On Noise Source Identification Of Split Unit Air Conditioner System - M. S. M., Sani; M. M., Noor; M. H. A., Rasid; M. R. M., Rejab; K., Kadirgama; M. M., Rahman (2009)

(untitled)
This paper presents the procedures and the results of noise source at the split unit air conditioner system. Noise in split unit air conditioning system is a frequent problem for the air conditioner manufactures. Split unit air conditioners have an indoor unit and an outdoor unit connected by communication pipes. Noise can reduce the efficiency and performance of the air conditioner. In order to identify and analysis of noise at air conditioner system, experimental have been done using sound intensity mapping method. The investigation was carried out by varying the parameter which is the fan speed and temperature at air conditioner. In order to identify where the noise source comes from, a grid rig had been build to get the noise location and their rating by located the microphone at the rig point. The signal from the probe will be analyze by using Pulse LabShop software. The results from the noise were showed in noise mapping with different color which indicates the different level of noises from different location. The highest noise sound levels occur at the front side of air conditioner which is at the fan that is about 74.784dB. The second highest noise sound level is occur at the right side which is at the compressor about 72.115dB. It can be concluded that sound power level will increase as higher as fan speed at the lowest temperature of the air conditioner.